2021
DOI: 10.3389/fmicb.2021.700138
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dietary Supplements Containing Viable Bacteria by Cultivation/MALDI-TOF Mass Spectrometry and PCR Identification

Abstract: The insufficient quality of products containing beneficial live bacteria in terms of content and viability of labelled microorganisms is an often-reported problem. The aim of this work was to evaluate the quality of dietary supplements containing viable bacteria available in Slovenian pharmacies using plate counting, matrix-assisted laser desorption ionisation time-of-flight mass spectrometry (MALDI-TOF MS) and species- or subspecies-specific PCR with DNA isolated from consortia of viable bacteria, from indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
1
11
0
1
Order By: Relevance
“…These results correlate with the evidence that MALDI-TOF MS has been shown to fail in identifying some species when the number of species-and strain-specific spectra included in the MALDI database is low [45]. A previous study suggested that the development of a dedicated in-house library containing MALDI TOF MS spectra of various reference strains could improve the identification accuracy [46]. Metagenomic sequencing misidentified L. helveticus in Microbiosys.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These results correlate with the evidence that MALDI-TOF MS has been shown to fail in identifying some species when the number of species-and strain-specific spectra included in the MALDI database is low [45]. A previous study suggested that the development of a dedicated in-house library containing MALDI TOF MS spectra of various reference strains could improve the identification accuracy [46]. Metagenomic sequencing misidentified L. helveticus in Microbiosys.…”
Section: Discussionsupporting
confidence: 76%
“…In fact, in a previous study analyzing the quality of dietary supplements sold in Slovenia, MALDI-TOF MS alone was not accurate in distinguishing some closely related Lactobacillus species. In these cases, the correct identification was obtained by pairing MALDI-TOF MS with species-specific PCR [46].…”
Section: Discussionmentioning
confidence: 99%
“…M. Hajjar et al 70 utilized MALDI TOF in negative-ion MALDI-TOF for the analysis of LPS or lipid A preparations to identify Francisella tularensis strains. In the food industry, the technique has been employed for evaluating dietary supplements containing live bacteria, as shown by Lorbeg et al 71 In plant research, Wang et al 72 used it for studying lipid distribution in peanut seeds. Importantly, in the realm of microbial identification, particularly for closely related or drug-resistant strains, MALDI’s role is being increasingly recognized.…”
Section: Resultsmentioning
confidence: 99%
“…W dostępnych na polskim rynku preparatach zawierających bakterie probiotyczne często spotykana jest zbyt mała liczba drobnoustrojów lub mniejsza liczba gatunków, niż producent deklarował na opakowaniu. Bardzo często obserwuje się niską przeżywalność lub jej brak, zwłaszcza w przypadku bakterii z rodzaju Bifidobacterium spp., w komercyjnych suplementach diety i preparatach medycznych [1,3,19,22,34]. Drobnoustroje te są beztlenowymi, nieruchliwymi, Gram-dodatnimi i nietworzącymi przetrwalników pałeczkami [5].…”
Section: Wprowadzenieunclassified